Role centrality, gender role ideology and work-family conflict among working fathers in South Africa - Gelb, Josh Adam (Department of Psychology, 2015)
This study examined role centrality and gender role ideology as antecedents of workfamily conflict amongst white-collar working fathers in South Africa (N = 369). Crosssectional, self-report survey data was collected. Exploratory factor analysis supported the bidirectional nature of work-family conflict. Interestingly, work and family role centrality did not explain a significant variance in work-family conflict, however hierarchical multiple regression analysis confirmed that when family centrality interacted with gender role ideology a significant variance of both family-to-work conflict and work-to-family conflict was explained. Moreover supporting a cross-domain relationship between family centrality and work-to-family conflict when interacting with gender role ideology. In the absence of variables interacting with gender role ideology, no significant relationship was found between role centrality and work-family conflict. Theoretical contributions and managerial implications are discussed.